Dampak Globalisasi terhadap Eksistensi Budaya - Andika (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2021)
Globalization as a door to step into the outside world. Interacting with the outside world, but the entry of globalization does not only have positive impacts but also negative impacts. Globalization shifts the values ​​of nationalism and culture that already exist in Indonesia. Globalization creates various problems in the cultural field, for example: loss of the original culture of a region or a country, erosion of cultural values, a decrease in nationalism and patriotism, loss of kinship and mutual cooperation, loss of self-confidence, a lifestyle that is not in accordance with custom we. Therefore it is necessary for us to limit which scope of globalization should be applied and which should be rejected.